Experimental research of retaining walls with structural surface - Timchenko, Radomir; Krishko, Dmytro; Savenko, Volodymyr (Academic journal Industrial Machine Building Civil Engineering, 2018)
The retaining walls are one of the most widespread types of engineering structures. Behaviour numerous studies of various soils with soaking have showed that their bearing capacity and compliance are closely related to their moisture content degree. To obtain information on the displacements and sediments of model structures and grounds, the hour-type indicators are used. The carried out researches have shown that with the same ground base, loading and boundary conditions, evident for a retaining wall with a structural surface, there is an inclusion in entire soil massif work. The uniformity of the structures and the ground base general deformations, in turn, provides retaining wall with a structural surface greater stability.
Keywords: experimental results; retaining wall; structural surface